Fabrication and cell imaging of konjac glucomannan-copper nanocluster conjugates with aggregation-induced emission. (26th May 2021) - Guan, Lianxiong; Liu, Wei; Kang, Huiting; Tian, Dating
Abstract: A positively charged konjac glucomannan- graft -poly-(2-methacryloyloxyethyl) trimethyl ammonium chloride (KGM- g -PDMC) was prepared by using ceric ammonium nitrate as the initiator in aqueous solution. Negatively charged copper nanoclusters (CuNCs) were prepared by a one-step reduction method using glutathione as the reductant. Then, the two precursors mentioned above were combined through electrostatic attraction to form a conjugate (KGM- g -PDMC/CuNCs) exhibiting aggregation-induced emission (AIE). The resultant products were characterized by Fourier transform infrared spectroscopy, zeta potential and particle size analysis, X-ray photoelectron spectrometry, transmission electron microscopy, and fluorescence spectrophotometry. The results showed that KGM- g -PDMC enhanced the AIE effect of CuNCs, with an approximate 4-fold increase in fluorescence intensity. A cytotoxicity analysis showed that the products possess good biocompatibility. Moreover, cell imaging indicated that the products have potential for application in the field of biomedicine. Graphical abstract: Image 1 Highlights: KGM-g-PDMC/CuCNs were facilely prepared through electrostatic attraction. KGM- g -PDMC enhanced the AIE effect of CuCNs. The resultant conjugates exhibited good biocompatibility and cell imaging performance.